Association of systemic immune-inflammatory index with in-stent restenosis in patients with and without diabetes mellitus - Xunwei Deng; Xunwei Deng; Xunwei Deng; Qiaoting Deng; Qiaoting Deng; Qiaoting Deng; Qunji Zhang; Qunji Zhang; Qunji Zhang; Jingyuan Hou; Jingyuan Hou; Jingyuan Hou (Frontiers in Cardiovascular Medicine)
BackgroundSystemic inflammation plays a vital role in the pathogenesis and prognosis of cardiovascular disease (CAD). The systemic immune-inflammation index (SII) has been developed as a cost-effective and practical predictor for CAD outcomes. This study aimed to determine the association between the SII and the risk of ISR among ACS patients with and without diabetes mellitus (DM).MethodsIn this retrospective cohort study, a total of 1,652 patients who underwent percutaneous coronary intervention (PCI) from February 2015 to December 2020 and were finally enrolled after follow-up with coronary angiography. The SII was calculated based on neutrophil, platelet and lymphocyte counts. Multivariable logistic regression models were employed to assess the associations between SII and ISR prevalence. Additionally, the interaction test and subgroup analysis were performed to evaluate the robustness of our findings. Furthermore, restricted cubic splines analysis was applied to visualize the relationship between the SII and the risk of ISR. Employing Spearman's rank correlation analysis to investigate the relationship between SII levels and the time to ISR occurrence.ResultsIn the whole cohort enrolled in this study, 128 (7.7%) participants developed angiographic evidence of ISR. The results demonstrated that the SII level significantly increased in patients with ISR compared to those with non-ISR, and these findings were similar in patients with and without DM. After adjusting for confounders, the multivariate logistic regression analysis revealed that participants with higher SII levels had a significantly increased risk of ISR for diabetics (all P < 0.05), and this significant association was observed in patients with more severe ISR (triple-coronary artery lesions). Additionally, RCS analysis reveals that there is a J-shaped nonlinear correlation between SII and ISR in the entire study cohort with (P for overall <0.001, and P for nonlinearity = 0.0058, respectively). Moreover, a threshold effect can be observed in the entire cohort, with an inflection point at the log2-SII value of 9.276 (SII = 620). Specifically, increased SII was linearly associated with ISR in diabetics (P for overall = 0.0007 and P for nonlinearity = 0.4316, respectively), indicating that the correlation between SII and ISR is stronger in diabetic patients than in those without diabetes. Spearman's rank correlation analysis demonstrated that elevated SII levels are related to earlier ISR onset in diabetics (r = −0.272, P = 0.049).ConclusionOur study suggests that SII may be an affordable and convenient marker that could be applied to predict the risk of ISR among ACS patients. Moreover, the study emphasized that high SII is an independent predictor of more severe and earlier ISR and may be helpful for patients' risk stratification, especially those with comorbid DM.